Die zersplittere Oekumene der HistorikerInnen. Historiographie in Kroatien in den 1990er Jahren - Iveljić, Iskra (Array, 2003)
Die zersplittere Oekumene der HistorikerInnen. Historiographie in Kroatien in den 1990er Jahren